Genesis and geological significance of intrusive rocks in the Lalinggaolihe iron deposit, east Kunlun, NW China: evidence from geochronology, petrological geochemistry, and Hf isotopes - Liu, Yuanlin; Chen, Chao; Lv, Xinbiao; Xu, Rongke; Zhang, Delong; Liu, Hongyu; Zhang, Zhongcheng (Frontiers in Earth Science, 2025)
The Lalinggaolihe mining area, situated in the southeastern Qimantag Mountain within the East Kunlun Orogen, hosts skarn-type Fe–Cu–Zn polymetallic deposits and is characterized by widespread intrusive rocks. LA-ICP-MS zircon U–Pb dating indicates that monzogranites in the northern part of the mining area yielded weighted mean ages of 216.22 ± 0.96 and 215.3 ± 2.1 Ma, whereas monzogranites, granodiorites, and dark diorites in the southern part yielded weighted mean ages of 415.8 ± 1.3, 417.1 ± 2.8, 416.7 ± 1.9, 414.6 ± 1.2 Ma. The northern and southern intrusions were formed during the Early Devonian and Late Triassic, respectively. The northern monzogranites exhibit high SiO2 (75.72%–77.36%), high alkali (K2O+ Na2O = 7.51%–8.39%), low CaO (0.58%–1.15%) and MgO (0.20%–0.26%) contents. They are enriched in light rare earth elements (LREE), depleted in Sr, U, and Eu, and display elevated TFeO (>1.0%), high TFeO/MgO ratios (>1), and high crystallization temperatures (811 °C), all consistent with A-type granite characteristics. Contrastingly, the southern monzogranites, granodiorites, and diorites have aluminum saturation indices (A/CNK) ranging from 0.82 to 1.09, classifying them as metaluminous to weakly peraluminous. These rocks belong to the high-potassium calc-alkaline series and are depleted in Nb, Ta, U, and Hf and are enriched in LREE. They contain minor amphibole, with TZr (closure temperatures for zircon) ranging from 739 °C to 746 °C for the monzogranites and granodiorites, and 724 °C for the diorites, characteristics consistent with I-type granites. Zircon Hf isotopic results reveal that the northern monzogranites have εHf(t) values ranging from −4.17 to −1.2, whereas the southern monzogranites, granodiorites, and dark diorites exhibit εHf(t) values ranging from −3.54 to 1.10, −4.3 to −0.27, and −2.86 to −1.16, respectively. These predominantly negative εHf(t) values suggest that the magmas were primarily derived from the partial melting of ancient crustal materials, with potential mixing of mantle-derived components. Comprehensive analysis indicates that the northern and southern intrusions formed during the post-collisional extensional stage of the Early Devonian and the collisional to post-collisional stage of the Late Triassic, respectively. These intrusions likely originated from the underplating of mantle-derived magmas mixed with crustal materials, with Fe polymetallic mineralization resulting from crust–mantle material exchange.